Relationship marketing : strategy and implementation - Peck, Helen; ScienceDirect eBooks (Oxford : Butterworth Heinemann, 1999)
Arranged in 6 sections, this title gives marketing practitioners and students critical examples of best practice from a variety of companies. Alongside 'Relationship Marketing: bringing quality, customer service and marketing together' and 'Relationship Marketing for Competitive Advantage: winning and keeping customers' this new title provides readers with insights into marketing in the 21st century. Major addition to relationship marketing literature Supports the relationship marketing titles that we already publish successfully Author team are amongst the UK's leading authorities in the sector.
1 Relationship marketing: The six markets framework 1 -- 2 The customer market domain: Managing relationships with buyers, intermediaries and consumers 33 -- 3 The supplier and alliance market domain 161 -- 4 The referral and influence market domains 220 -- 5 The recruitment and internal market domains 301 -- 6 Creating and implementing relationship marketing strategies 406.
"Published in association with the Chartered Institute of Marketing."
Series statement on jacket.
Includes bibliographical references and index.
Print version record.
Elsevier
Keywords: Relationship marketing; Marketing relationnel; BUSINESS & ECONOMICS -- Customer Relations; Relationship marketing; Relatiemarketing; Electronic books